Higher-Order Thinking Skills in Prospective Physics Teacher - Kaharuddin Arafah; Ruslan Ruslan; Nurhayati Nurhayati; Aeman Hakim; Agriani Pongkessu (Jurnal Penelitian Pendidikan IPA, 2022)
The rules regarding the assessment carried out by teachers have been refined to match the demands of 21st-century learning, the aspect that has been improved is the cognitive aspect, specifically in the assessment of Higher Order Thinking Skills. However, prospective teachers and even teachers still have difficulty implementing this assessment. The purpose of this study was to determine the profile of the ability of prospective physics teacher students in solving Higher Order Thinking Skills questions as an initial description in identifying problems that occur. This research was a descriptive study to determine the profile of postgraduate students at Makassar State University, South Sulawesi. The research data was obtained through test technique. These questions consist of 40 sets of items, with indicators of analyzing, evaluating, and creating. It has been developed by researchers and validated by experts. The percentage of the score obtained is 68, 79, and 55% for indicators of analyzing, evaluating, and creating respectively. Therefore, Prospective physics teachers can still be said to be unsatisfactory in solving Higher Order Thinking Skills questions.